2005
DOI: 10.1091/mbc.e04-12-1066
|View full text |Cite
|
Sign up to set email alerts
|

High Mobility of Flap Endonuclease 1 and DNA Polymerase η Associated with Replication Foci in Mammalian S-Phase Nucleus

Abstract: Originally detected in fixed cells, DNA replication foci (RFi) were later visualized in living cells by using green fluorescent protein (GFP)-tagged proliferating cell nuclear antigen (PCNA) and DNA ligase I. It was shown using fluorescence redistribution after photobleaching (FRAP) assay that focal GFP-PCNA slowly exchanged, suggesting the existence of a stable replication holocomplex. Here, we used the FRAP assay to study the dynamics of the GFP-tagged PCNA-binding proteins: Flap endonuclease 1 (Fen1) and DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 72 publications
3
9
0
Order By: Relevance
“…The high mobility of pol in human cells, both uniformly distributed and in foci, agrees with the observations of Solovjeva et al (2005) using Chinese hamster cells, and emphasizes that even though visible in fluorescent replication structures, proteins may still interact there very transiently. Our biochemical data suggest that pol may be associated with another protein in a complex of total molecular mass of 112 kDa.…”
Section: Discussionsupporting
confidence: 84%
“…The high mobility of pol in human cells, both uniformly distributed and in foci, agrees with the observations of Solovjeva et al (2005) using Chinese hamster cells, and emphasizes that even though visible in fluorescent replication structures, proteins may still interact there very transiently. Our biochemical data suggest that pol may be associated with another protein in a complex of total molecular mass of 112 kDa.…”
Section: Discussionsupporting
confidence: 84%
“…The N-terminal GFP-CSA did localize to the nucleoplasm (but not the nucleolus), but was more prominently distributed to the cyctoplasm (Figure S5A). Conversely, the C-terminal GFP-CSA was primarily detected in the nucleoplasm, as would be expected for CSA based on prior reports 46, 49-51 , with little nucleolar localization (Figure S5A). Consistent with C-terminal GFP-CSA retaining normal folding and activity, we found that the fusion protein corrected the UV sensitivity of CS3BE CSA mutant cells (Figure S5B).…”
Section: Resultssupporting
confidence: 78%
“…This would be accomplished by recruitment mechanisms. Indeed, the residence time of polη in replication foci of cells that have not been damaged is very short [30]. …”
Section: Discussionmentioning
confidence: 99%